2020
DOI: 10.1177/2050313x20919600
|View full text |Cite
|
Sign up to set email alerts
|

A case of sporotrichosis infection mimicking pyoderma gangrenosum and the role of tissue culture in diagnosis: A case report

Abstract: Sporotrichosis infections may cause cutaneous lesions mimicking other infectious or non-infectious causes such as pyoderma gangrenosum. We present a case of cutaneous sporotrichosis misdiagnosed as pyoderma gangrenosum and treated with immunosuppressants for 17 months leading to exacerbation and atypical morphology mimicking Histoplasma organisms on biopsy. Exclusion of infection prior to diagnosing pyoderma gangrenosum is important to prevent iatrogenic immunosuppression, demonstrating the challenges with app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Many reports have shown features of the disease mimicking pyoderma gangrenosum. 4,5 The typical histopathology of sporotrichosis reveals a mixed granulomatous and pyogenic inflammatory process. Characteristic structures, such as oval or cigar-shaped yeasts and mycelial and asteroid bodies, are found in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown features of the disease mimicking pyoderma gangrenosum. 4,5 The typical histopathology of sporotrichosis reveals a mixed granulomatous and pyogenic inflammatory process. Characteristic structures, such as oval or cigar-shaped yeasts and mycelial and asteroid bodies, are found in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 publications related to sporotrichosis were found in North America [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. There were 1460 patients in total associated with infection caused by species of the genus Sporothrix .…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
“…There were 1460 patients in total associated with infection caused by species of the genus Sporothrix . According to the previous classification, it was found that in Canada, only two case reports were found, one from Ontario and the other from Toronto [ 5 , 6 ]. In the US, 27 reports containing 1 clinical case were found (81.5% S. schenckii , 18.5% Sporothrix spp., S. schenckii complex, and S. schenckii sensu lato ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
See 2 more Smart Citations